Efeito alelopático de extratos de plantas medicinais e condimentares sobre a germinação e o desenvolvimento inicial do meloeiro - (:unkn) unknown (Universidade Federal do Pampa, 2012)
Allelopathy refers to the ability of certain plant has to interfere both positively and negatively on the growth of another plant through the secondary metabolites. The objective with this study was to evaluate the allelopathic activity of aqueous extracts of leaves of the false boldo (Plectranthus barbatus Andrews.), rosemary (Rosmarinus officinalis L.), Basil (Ocimum basilicum L.) and marjoram (Origanum majorana L.) on the germination and early development of melon. Only the leaves were used for the production of the extracts, at concentrations of 2 to 8%. To analyze the influence of extracts on germination, melon seeds were distributed in petri dishes lined with germination paper, moistened with extract or water, and kept in an incubator. The evaluation consisted of germination (PG), germination speed index (GSI), length of shoot and root. To analyze the influence of extracts on the growth, melon seeds were germinated on distilled water and transferred to incubator containing germination paper moistened with extract or water, remaining in an incubator. The evaluation consisted of the root length and shoot and fresh weight of seedlings. There were significant interactions between the factors plant extracts and concentrations of aqueous extracts for the index of germination rate, shoot, root and green mass, but there were no interactions between the factors plant extracts and concentrations of aqueous extracts for germination. Based on these results we can infer that the germination of melon does not occur allelopathic interference of aqueous extracts used, but for the index of germination speed occurs inhibition by aqueous extract of rosemary. For the initial development, the aqueous extracts and rosemary inhibit false boldo and basil and marjoram stimulate the development of shoot and root of melon.
Keywords: Cucumis melo L.; Metabólitos secundários; Princípio ativo; Secondary metabolites; Active principle; CNPQ::CIENCIAS AGRARIAS